A method of using image-view pairs to represent complex 3D objects. Issue 1 (1st January 2018) - Luo, Lihong; Mo, Jianqing; Yang, Xian
Abstract: Manually building models of complex objects is usually very difficult. 3D scanning can provide accurate models, but the required processing of very large data sets is time-consuming and not suitable for real-time applications. This paper presents a novel method that uses a series of images to represent an object. Initially, we obtain many images by photographing in different spatial directions. Each image matches a vector of an observed direction. During real-time rendering, the image closest to the eye direction is selected and shown. We call this method of model building the image-view pairs (IVP) model. The IVP model can support dynamic shadows in addition to static shadows. This paper proposes a method based upon affine transformation and multitexturing. IVP objects also support collision detection. Experiments show that the proposed IVP objects look realistic and require less processing power and memory. Moreover, the displayed scene runs very smoothly. The proposed method can be very useful for large real-time applications.